(untitled) (Islas, 2025)
Introduction: Olympe de Gouges published the Declaration of the Rights of Woman and the Female Citizen (1791) in response to the exclusion of women in the Declaration of the Rights of Man and the Citizen (1789), written in specific masculine and later interpreted as generic. Methods: The semantic and discursive gender of both versions (masculine and feminine) of this foundational text of modern society is analysed as an intralinguistic translation, in order to determine the interpretative intention, marked or not, of the grammatical genders. In parallel, we outline the history of grammatical norms on gender and, in particular, the genericity of masculine. Results: The texts in this study exemplify the ambiguity of masculine gender and its disservice to women. On the one hand, the masculine gender of the original text was never interpreted as generic, but as excluding women. On the other hand, De Gouges’ feminist translation resorted to specific feminine, albeit with specific instances of generic masculine and inclusive language strategies. The use and absence of linguistic genders reproduce the feelings of men and women of the time about their own current and desired identities, as well as that of others. Conclusions: Patriarchy has normalised and naturalised its superiority through generic masculine, which allows it to subordinate, exclude and weaken the position of women through language. Its use in legal texts jeopardises the access to rights for the unnamed half of the population. Faced with the current threat of regression of social advances, it is urgent to reject this patriarchal norm and to rewrite legal texts in inclusive language that makes women visible, dignifies and protects them.